The correlation between occupational performance and well-being in stroke patients - Chae, Gang-Seok (J Phys Ther Sci, 2016)
[Purpose] This study was performed to evaluate the occupational performance of stroke patients and their environment by occupational self-assessment and to investigate the relationship between occupational performance and well-being. [Subjects and Methods] This study enrolled ninety-two stroke patients who were receiving occupational therapy at a general hospital, a rehabilitation hospital, or a community welfare center in the cities of Busan and Gimhae, Republic of Korea. Occupational performance and well-being were investigated with Occupational Self-Assessment Version 2.2 and the Personal Well-being Index-Adult. [Results] Analysis of the correlation between occupational performance as assessed by the “Myself” and “My Environment” sections of Occupational Self-Assessment Version 2.2 and well-being revealed moderate positive correlation for both sections. [Conclusion] The relationship between occupational performance and well-being was identified. Further studies are needed to reveal whether improvement of occupational performance could affect well-being in various dimensions.